Role Relations in George Orwell’s 1984: Agency-Goal Analysis - Paudel, Prakash (The Batuk, 2021)
This research paper concentrates on George Orwell’s novel 1984, published in 1949. The novel explicates the ugly lifestyle of citizens under the rule of a powerful totalitarian ruler Big Brother. Being a ruler, the Big Brother has ultimate political power, and that is, in the narrative, linguistically asserted. This research paper examines how such political and social power of a character/person is imposed in the linguistic territory of a narrative in the light of Critical Discourse Analysis. Critical Discourse Analysis evaluates how the social and political agency of any person in any given discourse works in the linguistic form, theorists like Anthony Giddens elaborate on the role of agency in shaping the social structure. For the purpose of examining the agency in the narrative, with a particular focus on agency-patient role relation, this research brings in the role relations as the trope and, thus, concludes that totalitarian rulers drain out the agency of the citizens even in linguistic form, along with socio-political agency.